(untitled) (International Journal of Engineering and Computer Science, 2016)
In networking aggressive environment Disruption Tolerant Networking (DTN) method is widely used advances are broadly used in hostile environments for successful wireless communications. Applying ABE to DTN presents a few issues like Key revocation (or upgrade), Key escrow issue and Coordination of attributes issued from distinctive authorities. The CP-ABE gives a multiauthority scheme to secure information retrieval in decentralized DTNs where every secret key of an end user can be redesigned separately and instantly. Consequently the scalability and security can be enhanced in the proposed system.